Human Papillomavirus, Human Immunodeficiency Virus, and Oral Microbiota Interplay in Nigerian Youth (HOMINY): A Prospective Cohort Study Protocol - Jia Liu; Esosa Osagie; Paul Akhigbe; Nosakhare Idemudia; Ozoemene Obuekwe; Ruxton Adebiyi; Nicolas Schlecht; Yana Bromberg; Fidelis E Eki-Udoko; Nosayaba Osazuwa-Peters; Modupe Oluseun Coker (BMJ Open)
Introduction Persistent oral infections with high-risk human papillomavirus (HR-HPV) are a potential cause of most oropharyngeal cancers (OPCs). Oral HR-HPV infection and persistence are significantly higher in people living with HIV (PLWH). Most data on oral HR-HPV in PLWH come from developed countries or adult cohorts. This study aims to investigate oral HR-HPV susceptibility and persistence among children and adolescents living with HIV (CALHIV) and to understand the roles of perinatal HIV exposure, infection, antiretroviral treatment, and the oral microbiome.Methods and analysis This prospective cohort study is ongoing at the University of Benin Teaching Hospital (UBTH), Nigeria, involving mother-child pairs followed at 6-month intervals for 2 years. Participants include children aged 9–18 and their mothers aged 18 and above. The study targets 690 adolescents in three groups: 230 CALHIV, 230 HIV-exposed but uninfected and 230 HIV-unexposed and uninfected. Oral rinse, saliva, buccal swabs and supragingival plaque samples are collected at each visit. Blood samples are tested for HIV, Hepatitis B virus (HBV) and Hepatitis C virus (HCV), with CD4, CD8 and full blood counts performed. Oral HPV is assessed for incidence, persistence, and clearance. Statistical analyses to look for associations between cohort baseline characteristics and findings will be conducted using univariable and multivariable models for repeated data and high-dimensional microbiome data. All statistical tests will be two-sided; a p value <0.05 will indicate significance. Multiple comparisons will be adjusted using the False Discovery Rate (FDR) correction to control for Type I error.Ethics and dissemination The study was approved by Rutgers State University (Pro2022000949) and the UBTH (ADM/E22/A/VOL. VII/14813674). Informed consent was obtained from all parents/guardians.